DIGITAL TRANSFORMATION AS A TOOL FOR IMPROVING THE MANAGEMENT OF STRATEGIC ENTERPRISE DEVELOPMENT - RYBAK, Ihor; GARAFONOVA, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to an in-depth study of the role of digital transformation as a fundamental tool for enhancing the strategic management of enterprise development in the context of global technological and economic change. The paper comprehensively analyzes the conceptual essence of digital transformation within the framework of strategic management theory and practice, emphasizing its influence on the efficiency of managerial decisions, organizational adaptability, and long-term business competitiveness. It is demonstrated that the integration of digital technologies significantly transforms the logic of strategic planning, resource allocation, and performance evaluation within modern enterprises. Particular attention is paid to the introduction of digital tools in data analytics, customer experience management, business process reengineering, and the creation of innovative business models. The study highlights that digital transformation serves not only as a technological upgrade but as a systemic change that reshapes corporate culture, leadership approaches, and stakeholder relations. It fosters the development of new management paradigms based on the principles of agility, data-driven decision-making, and continuous innovation. The article substantiates that the use of big data, automation, and artificial intelligence allows enterprises to anticipate market trends more precisely, mitigate risks, and ensure strategic sustainability under conditions of uncertainty. The research results confirm that the effective implementation of digital technologies enhances productivity, strengthens competitive advantages, and promotes sustainable and inclusive growth. The paper also outlines practical recommendations for improving strategic management through digital innovation, including the formation of a digital-oriented organizational culture, the development of digital competencies among employees, and the active use of analytical platforms and decision-support systems. These measures collectively ensure that enterprises can maintain adaptability, resilience, and long-term development in the era of digital economy.